2002
DOI: 10.2527/2002.8082122x
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: The effect of freezing on Warner-Bratzler shear force values of beef longissimus steaks across several postmortem aging periods

Abstract: The objective of this study was to compare fresh and frozen protocol procedures for Warner-Bratzler shear force (WBSF) determination on steaks aged for different periods of time. The fresh protocol consisted of measuring WBSF on steaks cooked on the exact day the aging period ended. The frozen protocol consisted of measuring WBSF on steaks that were aged, frozen (-16 degrees C) for approximately 2 mo, thawed for 24 h, and then cooked. Twenty-two strip loin steaks from each of 20 crossbred heifers and steers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 15 publications
4
52
2
19
Order By: Relevance
“…A negative correlation between cooking loss and juiciness was reported by Jung et al (2016) and Aaslyng et al (2003) for beef and pork, respectively. According to the literature, the shear force value of meat decreases after freezer storage (Shanks et al, 2002;Farouk & Freke 2008;Lagerstedt et al, 2008), which points to improved tenderness. This is attributed to the enzymatically induced autolysis of muscle fibres during meat ageing before freezing and the loss of structural integrity of muscle fibres caused by ice crystals during freezing (Vieira et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A negative correlation between cooking loss and juiciness was reported by Jung et al (2016) and Aaslyng et al (2003) for beef and pork, respectively. According to the literature, the shear force value of meat decreases after freezer storage (Shanks et al, 2002;Farouk & Freke 2008;Lagerstedt et al, 2008), which points to improved tenderness. This is attributed to the enzymatically induced autolysis of muscle fibres during meat ageing before freezing and the loss of structural integrity of muscle fibres caused by ice crystals during freezing (Vieira et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized this is due to all steaks being subjected to cooking without freezing, which commonly occurs during WBSF analysis (Shanks et al, 2002). In their review of the literature, Garmyn and Miller (2014) concluded that use of implants and ZH during finishing increases WBSF; however, retail studies would indicate these technologies elicit no adverse effects on objective or subjective tenderness measures.…”
Section: Growth-promoting Technologies Effectsmentioning
confidence: 99%
“…Previous studies evidence a correlation between cooking losses and the ageing process. Shanks et al (2002) showed that muscle loses ability to preserve humidity with ageing, while Wu et al (2006) conclude that higher cooking losses in aged meat can be due to protein aggregation after ageing. Furthermore, Straadt et al (2007) noticed that extended ageing associates with the growth of cooking losses while microstructural alterations occurring in ageing result in severe structural alterations.…”
Section: Cooking Lossmentioning
confidence: 99%